2024
DOI: 10.3390/ijms25063513
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Aquaporins in Brain Disease”

Miriam Echevarría,
Pablo García-Miranda

Abstract: Water is an abundant and important component of the human brain, the homeostasis of which is rigorously controlled [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Our most recent studies have demonstrated that AQP4 expression is clearly associated with myelination in areas of white matter, as in the CC and cerebellum in the brains of mice [6,7]. Additionally, we identified a population of CD11c+ microglia in the mouse periaqueductal zone [8], similar to the one detected by other authors in the CC and cerebellum, which had been reported to be very important in maintaining these tissues' myelinisation and neurogenesis in WT mice [4].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our most recent studies have demonstrated that AQP4 expression is clearly associated with myelination in areas of white matter, as in the CC and cerebellum in the brains of mice [6,7]. Additionally, we identified a population of CD11c+ microglia in the mouse periaqueductal zone [8], similar to the one detected by other authors in the CC and cerebellum, which had been reported to be very important in maintaining these tissues' myelinisation and neurogenesis in WT mice [4].…”
Section: Discussionsupporting
confidence: 67%
“…Recently, we demonstrated that aquaporin-4 (AQP4) expression is clearly associated with the early cell differentiation process that leads to myelination in areas of white matter in mice brains, such as in the CC and cerebellum [6,7]. We also identified, for the first time, a population of CD11c+ microglia in the periaqueductal zone of AQP4-knockout (KO) animals similar to that detected by other authors in the CC and cerebellum, which is believed to be important for maintaining the myelinisation and neurogenesis of these tissues in WT mice [4].…”
Section: Introductionmentioning
confidence: 99%